Modelling of burner stabilised oxy-fuel flames by using non-premixed and partially-premixed turbulent combustion models. (20th November 2006) - Van Rossum, M.C.; Bastiaans, R.J.M.; Roekaerts, D.J.E.M.; De Goey, L.P.H.
The turbulent flow and combustion process of oxy-fuel flames are studied in the wake behind a burner rim separating fuel and oxidiser inlet channels. A range of conditions was considered, from stably attached flames, via lifted flames to blow-off. It was found that the chemical equilibrium model did not predict the chemical composition well. The laminar flamelet model performed better. It appeared that extinction is not the mechanism that leads to a lifted flame and therefore partial premixing was considered. It appeared that lifted oxy-fuel flames can be predicted fairly well by adjusting a turbulent burning velocity constant.